Biodegradasi Dari Penyalut Layak Makan Berbasis Pati Sagu - Khairun Nisah; Basuki Wirjosentono (Elkawnie, 2015)
The experiment about the food to cauting decent from starch of sago using powder of bar sago palm as filler and glycerol as plastisizer has done. Biodegadation of to cover eat decent eith powder of bar sago palm as filler, was done by soil buriar test for 5 – 3 days. Mean while biodegadation in Aspergillus niger media was done for 3-5 days. The results of weight loss percentage showed that all to cover eat decent can be biodegadation rate. The biodegadability by soil burial test was more faster thant by Aspergillus niger fungi. Characterization of fungtional goups were done by FT – IR and the morphology was tested by SEM. Toxicity test using E.Coli in Nutrien Agar media at temperature 370C and incubation 48 hours showed that to cover eat decent not indivcatoin of anticeptic properties.